ESI‐MS2 and Anti‐inflammatory Studies of Cyclopropanic Triterpenes. UPLC‐ESI‐MS and MS2 Search of Related Metabolites from Donella ubanguiensis. Issue 1 (January 2017) - Sandjo, Louis P.; Nascimento, Marcus V.P. dos Santos; da Silva, Layzon A.L.; Munhoz, Antonio C.M.; Pollo, Luiz A.E.; Biavatti, Maique W.; Ngadjui, Bonaventure T.; Opatz, Till; Fröde, Tania S.
Abstract: Introduction: Triterpenes are one of the largest secondary metabolites groups spread in the plant kingdom with various skeletons. These metabolites have showed various bioactivities including anti‐inflammatory activity. Objective: The study aims to explore the mass spectrometry fragmentation of donellanic acids A‐C (DA A–C), three compounds identified from Donella ubanguiensis ; in addition, the fragmentation behaviour of these metabolites will serve as a fingerprint to search and characterise triterpenes congeners in fruits, bark and wood crude extracts of D. ubanguiensis . This work was prompted by the anti‐inflammatory activity on leukocyte migration, exudate concentrations and myeloperoxidase activity obtained for DA A–B. Methodology: The bioactivity was performed on mouse model of pleurisy induced by carrageenan and the parameters were analysed by veterinarian automated cell counter and colorimetric assays. While the tandem mass analyses of DA A–C were carried out by a direct infusion ESI‐QTOF‐MS/MS, the extracts were studied by UPLC‐ESI‐QTOF‐MS and UPLC‐ESI‐QTOF‐MS/MS. Results: DA A displayed interesting anti‐inflammatory activity by inhibiting leukocyte migration, exudate concentrations and myeloperoxidase activity ( p < 0.05) while DA B was weakly active ( p > 0.05). Moreover, the diagnostic of the MS 2 behaviour of DA A–C in conjunction with the chromatograms and the obtained MS 2 data of the crude extract led to the characterisation of three cyclopropane triterpenes (T1–T3) and six saponins (T4–T9) from the fruits, the bark, and the wood extracts. Conclusions: Donella species deserve more investigation since metabolites related to the anti‐inflammatory compound (DA A) could be identified. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The anti‐inflammatory effect obtained for donellanic acid A prompted us to study its tandem ESI‐QTOF‐MS fragmentation as well as those of donellanic acids B and C. Furthermore, the MS 2 behaviour of the three metabolites obtained previously from Donella ubanguiensis, served as a fingerprint to characterize other related triterpenes in the fruits, bark and wood crude extracts of the same plant. UPLC‐ESI‐QTOF‐MS and ‐MS 2 data of these extracts allowed the characterization of three cyclopropane triterpenes and six saponins.